2015
DOI: 10.1038/jid.2015.288
|View full text |Cite
|
Sign up to set email alerts
|

Activating CARD14 Mutations Are Associated with Generalized Pustular Psoriasis but Rarely Account for Familial Recurrence in Psoriasis Vulgaris

Abstract: Caspase recruitment family member 14 (CARD14, also known as CARMA2), is a scaffold protein that mediates NF-κB signal transduction in skin keratinocytes. Gain-of-function CARD14 mutations have been documented in familial forms of psoriasis vulgaris (PV) and pityriasis rubra pilaris (PRP). More recent investigations have also implicated CARD14 in the pathogenesis of pustular psoriasis. Follow-up studies, however, have been limited, so that it is not clear to what extent CARD14 alleles account for the above cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
100
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 103 publications
(104 citation statements)
references
References 31 publications
0
100
0
3
Order By: Relevance
“…Recently, several mutations in CARD14 (also known as CARMA2 or Bimp2) were identified in both familial and nonfamilial cases of psoriasis, pinpointing CARD14 as the susceptibility gene of the elusive psoriasis susceptibility locus 2 (PSORS2) in chromosomal region 17q25 [3][4][5][6]. Human CARD14 is a 1,004 amino acid long protein that is characterized by a C-terminal membrane-associated guanylate kinase (MAGUK) domain, which is a structural module composed of a PDZ, SH3, and guanylate kinase-like (GUK) domain.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several mutations in CARD14 (also known as CARMA2 or Bimp2) were identified in both familial and nonfamilial cases of psoriasis, pinpointing CARD14 as the susceptibility gene of the elusive psoriasis susceptibility locus 2 (PSORS2) in chromosomal region 17q25 [3][4][5][6]. Human CARD14 is a 1,004 amino acid long protein that is characterized by a C-terminal membrane-associated guanylate kinase (MAGUK) domain, which is a structural module composed of a PDZ, SH3, and guanylate kinase-like (GUK) domain.…”
Section: Introductionmentioning
confidence: 99%
“…Ist die Funktion des Antagonisten durch die genetische Variation vermindert, so überwiegen die proinflammatorischen Einflüsse der Agonisten. Zudem wurden bestimmte Variationen im CARD14-Gen identifiziert, die mit GPP assoziiert sind [4]. Die Prävalenz der GPP variiert und liegt bei etwa 1-9/1 Mio.…”
unclassified
“…There was a reduction of Bcl10 expression observed in the presence of all three CARD14 constructs in HEK293 cells (see Supplementary Figure S1b) and a decrease of CARD14 mutant expression in primary keratinocytes (Figure 1a). Previously, it has been suggested that CARD14 mutants associated with psoriasis are less soluble than WT CARD14 (Berki et al, 2015). Additionally, it has been previously described that Bcl10 forms oligomeric structures that can be nucleated by CARD11 (Qiao et al, 2013).…”
Section: Resultsmentioning
confidence: 99%